Water mass exchange between the Nordic Seas and the Arctic Ocean on millennial time scale during MIS 4–2 - Rasmussen, Tine Lander; Thomsen, Erik; Nielsen, Tove (Geochemistry, Geophysics, Geosystems, 2014)
The climate of the last glaciation circa 65,000–25,000 years ago was interrupted by about 15 abrupt temperature fluctuations, the so-called Dansgaard-Oeschger events consisting of warm interstadials and cold stadials recorded in Greenland ice cores. The largest fluctuations occur in the North Atlantic region, but they have been registered over the most of the world. The events are linked to changes in deep water formation in the Nordic seas and North Atlantic, disrupting the thermo haline circulation. Yet, Dansgaard-Oeschger events have so far not been recorded north of the convection areas in the central Nordic seas, and it is not known if they affected the water exchange between the Nordic seas and the Arctic Ocean. In this study, we analyze core JM05-31GC from the northern Fram Strait at the very entrance to the Arctic Ocean. The core contains sediments from marine isotope stages (MISs) 4–2. The results show millennial timescale shifts in all the investigated proxies including the distribution of planktonic and benthic foraminifera, planktonic and benthic oxygen and carbon isotopes, and several sedimentological parameters. In JM05-31GC, the interstadials are characterized by relatively high surface and low bottom water temperatures, low content of ice-rafted debris, and well-ventilated bottom water. Stadials are characterized by the presence of icebergs and decreasing surface water and increasing bottom water temperatures due to increased inflow of Atlantic subsurface water. Ventilation decreased during Heinrich events and mo st stadials. The results show that the Dansgaard- Oeschger events strongly affected the water exchange between the Nordic seas and the Arctic Ocean.